Perbedaan Pemberian Terapi Musik Klasik dan Musik Meditasi Terhadap Tingkat Kecemasan Pada Pasien Tindakan Odontektomi - Ramadhani, Silmi Agnia; mulyanti, sri; restuning, sekar; octaviana, devy (Jurnal Terapi Gigi dan Mulut, 2024)
Anxiety is very common in patients when visiting the dentist, especially when surgery is performed, such as odontectomy. Anxiety management is done by pharmacological and non-pharmacological means. Music is one of the non-pharmacological methods to trigger safe, cheap, and effective relaxation. Thus, a study was conducted on the difference between classical music therapy and meditation music on anxiety levels in odontectomy patients. The research method used was quasi experiment with Pretest-Posttest two group design. Subjects were 38 and divided into 2 groups, namely the treatment and control groups. Subjects were given informed consent, filled in subject identity data, in the treatment group filled out the MDAS (modifed dental anxiety scale) questionnaire before listening to classical music and meditation music and the control group was given a posttest after odontectomy with the same questionnaire. The purpose of this study was to determine the difference between classical music therapy and meditation music on anxiety levels in odontectomy patients. Statistical analysis using the Saphiro Wilk test. The results of this study are pretest / posttest classical music obtained a value of 14.21 / 6.63. The conclusion is that there is a difference in the provision of classical music therapy and meditation music on the anxiety level of odontectomy patients with a significant p-value of 0.000 (p <0.05), meaning that classical music is more effective than meditation music in reducing anxiety levels in odontectomy patients.